(untitled) (The Research of Medical Science Review, 2025)
Background: Upper Crossed Syndrome (UCS) is a postural condition characterized by abnormalities in the upper body, including increased thoracic kyphosis, rounded shoulders, and a forward head posture. The prevalence of UCS varies significantly, ranging from 11% to 60% across different populations and age group. Objective: The Objective was to Compare the effectiveness of Corrective Exercises and Alexander Technique on Pain and Quality of Life in Upper Cross Syndrome among Students. Methodology: Twenty-two males and females aged 18 – 25 years having upper cross syndrome over 6 weeks and positive Neck test and Flesche test were participated in this study. The study was conducted in Rehab Max clinic for a period of three months. The study participants were divided into two groups, Group A received corrective exercises, while Group B received Alexander technique. Pain intensity and quality of life were measured using Numerical Pain Rating Scale, and Quality of Life (SF-12) respectively at baseline, 3rd week and 6th week. Data was analyzed using SPSS version 24. Results: The results showed a significant difference at 3rd week and 6th week values for all outcome variables. The findings of current study found to be significant (p = < 0.05) within group analysis (Friedman test) and between group analysis (Man Whitney Test). Conclusion: Alexander Technique found to be very effective in decreasing pain intensity and improving quality of life with upper cross syndrome among students.